Thrombocytopenia Is an Independent Risk Factor for the Prognosis of Thrombotic Microangiopathy in Chinese Patients With Systemic Lupus Erythematosus - Yang, Fan; Tian, Junwei; Peng, Linyi; Zhang, Li; Liu, Jia; Tian, Xinping; Zhang, Wen; Li, Mengtao; Zhao, Yan; Zhang, Fengchun; Zeng, Xiaofeng; Wang, Li; et al. (Frontiers in Medicine, 2021)
Objectives: This study aims to describe clinical characteristics and outcome of thrombotic microangiopathy (TMA) in Chinese patients with systemic lupus erythematosus (SLE), and investigate the risk factors. Methods: We conducted a retrospective single-center cohort and enrolled patients of TMA associated with SLE between January 2015 and December 2018. Demographic characteristics, clinical features, laboratory profiles, therapeutic strategies, and outcomes were collected. The risk factors of TMA in patients with SLE for mortality using multivariate analysis were estimated. Results: A total of 119 patients with a diagnosis of TMA were enrolled within the study period in our center, and SLE was found in 72 (60.5%) patients. The median age was 29.2±10.1 and 65 (92.3%) were female. Only 15 patients were found with definite causes, the other 57 cases remained unclear reason. 62 patients got improved, while 10 patients died after treatment (mortality rate: 13.9%). Compared with the survival group, the deceased group had a higher prevalence of neuropsychiatric manifestations, infection with two or more sites, increased levels of C-reactive protein (CRP) and D-Dimer, and decreased platelet count. Multivariate analysis showed that the decrease of platelet count is the independent risk factor for in-hospital mortality for TMA in patients with SLE. The Receiver operating characteristics (ROC) curve analysis displayed that a cutoff value of＜18×10^9/L for platelet count could significantly increase the risk of death. Conclusions: TMA often occurs in active SLE patients with high mortality (13.9%), and thrombocytopenia, especially when the platelet count lower than 18×10^9/L, is the risk factor for death.